Necessary condition analysis (NCA): review of research topics and guidelines for good practice - Jan Dul; Sven Hauff; Ricarda B. Bouncken (Review of Managerial Science, 2023)
Necessary condition analysis (NCA) is an increasingly used or suggested method in many business and management disciplines including, for example, entrepreneurship, human resource management, international business, marketing, operations, public and nonprofit management, strategic management, and tourism. In the light of this development, our work delivers a review of the topics analyzed with NCA or in which NCA is proposed as a method. The review highlights the tremendous possibilities of using NCA, which hopefully encourages other researchers to try the method. To support researchers in future NCA studies, this article also provides detailed guidelines about how to best use NCA. These cover eight topics: theoretical justification, meaningful data, scatter plot, ceiling line, effect size, statistical test, bottleneck analysis, and further descriptions of NCA.
Keywords: C80; M1; 650; Necessary condition analysis; NCA; Review of topics in NCA; Method review; Guidelines